Prediction of Student Performance in a Series of Related Courses of the Undergraduate Program of the Department of Computer, Informatics and Telecommunications Engineering – International Hellenic University - Eleftherios, Panagis; Angeioplastis, Athanasios; Tsimpiris, Alkiviadis; Varsamis, Dimitrios (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
It is a fact that educational institutions at all levels are now focusing their attention on analyzing the behavior and performance of their students. The main objective of this study is to examine whether it is possible to predict the grades of students in the Department of Computer, Informatics and Telecommunications Engineering (ICT) at the International Hellenic University (IHU), in a course, based on their performance in previous related courses within real error margins, as well as the optimization of the prediction error. Different models were used for prediction in order to evaluate the performance and impact of each model separately. The goal of this work is to provide significant results regarding the long-term performance of the students. The models used were capable of predicting the performance within the defined absolut error margin.